Assemblage Structure of Larval Fishes in Epipelagic and Mesopelagic Waters of the Northern Gulf of Mexico - Verena H. Wang (Frontiers Media S.A., 2021)
The early life stages of fishes play a critical role in pelagic food webs and oceanic carbon cycling, yet little is known about the taxonomic composition and distribution of larval fishes in the northern Gulf of Mexico (GOM) below the epipelagic (<200 m). Here, we provide the first large-scale characterization of larval fish assemblages in the GOM across epipelagic, mesopelagic, and bathypelagic regions (0–1,500 m), using samples collected during the Natural Resource Damage Assessment conducted following the Deepwater Horizon oil spill (DWHOS). These data contain > 130,000 ichthyoplankton specimens from depth-discrete plankton samples collected across 48 stations in the GOM during six cruises conducted in 2010 and 2011. We examined indices of abundance and diversity, and used a multivariate regression tree approach to model the relationship between larval fish assemblages and environmental conditions. The total abundance of larval fish followed a generally decreasing trend with increasing depth, and family-level richness and diversity were significantly higher in the epipelagic than mesopelagic and bathypelagic regions. Fourteen distinct assemblage groups were identified within the epipelagic, with depth, surface salinity, and season contributing to the major branches separating groups. Within the mesopelagic, seven distinct assemblage groups were identified and were largely explained by variation in depth, season, and surface temperature. Bathypelagic assemblages were poorly described by environmental conditions. The most common epipelagic assemblage groups were widely distributed across the GOM, as were all mesopelagic assemblage groups, suggesting limited horizontal structuring of GOM larval fishes. Of the mesopelagic-associated fish taxa, four dominant families (Myctophidae, Gonostomatidae, Sternoptychidae, Phosichthyidae) comprised the majority of the catch in both the epipelagic (63%) and combined mesopelagic and bathypelagic (97%) regions. Dufrêne-Legendre indicator analysis confirmed that these dominant families were characteristic of epipelagic and mesopelagic assemblages; the larvae of less common mesopelagic-associated families largely identified with epipelagic assemblage groups. A lack of baseline data about the distribution patterns of early life stages of mesopelagic fishes in the GOM was apparent following the DWHOS, and these findings provide a valuable reference point in the face of future ecosystem stressors.